Biomechanical research in artistic gymnastics: a review - Prassas, S.; Kwon, Y. H.; Sands, W. A. (Sports Biomechanics, 2006)
Biomechanical research into artistic gymnastics has grown substantially over the years. However, most research is still skill oriented with few tries at generalization. Consequently, our understanding of the principles and bases of the sport, although improved, is still marginal with gaps in knowledge about technique attributes throughout the sport. For that reason, this review begins with an attempt to identify important variables contributing to successful performance. The review is presented in clusters of work in similar apparatuses culminating in Tables offering an 'at a glance' summary of knowledge in each cluster. The last section of the review tries to give some direction to future biomechanical research in gymnastics in issues relating to data collection--two-dimensional or three-dimensional, image size, frame rate--and analysis, such as descriptive or explanatory, simulation and optimization, and statistical issues.